Human Resource Optimization Strategy in Improving the Quality of Life of The Sendangdawung Village Community - Ananda Fathal Habba; Diah Syafitri; Laila Lathifah; Muhammad Nabil Muallif; Muhammad Irfan Khoiron; Wening Hartati (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Kuliah Kerja Nyata (KKN) is a form of education by providing student learning experiences in the community outside the campus. Through service activities to Sendangdawung Village, there is synergy with the Village Government, Agencies and the Community in various ways. The purpose of this service is to help the Village in order to optimize Human Resources through all activities, both constructive and sustainable. Service is carried out by participating in existing activities or making activities necessary for optimization purposes. The results of the service provide an overview of what needs to be added to existing activities and what needs to be presented in order to improve the quality of life of the Sendangdawung Village Community.